Effect of micro irrigation practices on growth and yield of garlic (Allium sativum L.) var. G. 41 - P C Tripathi, V Sankar, K E Lawande, (Journal of Spices and Aromatic Crops, 2008)
An experiment was conducted at Pune (Maharashtra) to study the feasibility of microirrigation on growth, yield and yield contributing characters of garlic (Allium sativum)under Western Maharashtra conditions. Both drip and sprinkler irrigation systems improvedgrowth, yield and yield contributing parameters of garlic. Among the different irrigationmethods and levels tested, drip irrigation at 100% PE recorded the highest marketable bulbyield of garlic followed by sprinkler irrigation at 100% PE. The study indicated that in thebest treatment compared to surface method of irrigation, a saving of 37.9% irrigation waterin drip and 36.4% in sprinkler system can be achieved.